Effect of selected dopants on conductivity and moisture stability of Li3PS4 sulfide solid electrolyte: a first-principles study. (June 2022) - Nikodimos, Y.; Su, W.-N.; Bezabh, H.K.; Tsai, M.-C.; Yang, C.-C.; Hwang, B.J.
Abstract: The first principle computational screening was performed to investigate the effect of selected dopants for Li3 PS4 sulfide solid electrolyte on its ionic conductivity and stability toward moisture. The results suggest that substitution P 5+ using isovalent cations whose electronegativity (EN) value is closer to the value of S has more significant effects on the ionic conductivity, whereby W 5+ and Sb 5+ can improve most. Similarly, aliovalent cation substitutions with compensating changes in the lithium-ion concentration, particularly those with a lower oxidation state and higher EN, such as Cu 2+, effectively enhance the lithium-ion conductivity in this structure. For cation dopants, it is found that ionic conductivity improvement of Li3 PS4 is the synergetic effect of EN and oxidation number of the dopant as well as the material's lattice parameter change. Oxides of the considered cation dopants can also improve the ionic conductivity of the material but have much lower lithium-ion conductivity than the cases of cation dopants. However, the metal oxide dopants, particularly those derived from soft Lewis' acid cations, show a marginal improvement in moisture stability of the Li3 PS4 electrolyte. The effect of halides and metal halide dopants on the lithium-ion conductivity and moisture stability of Li3 PS4 electrolyte are also studied. It is found that metal halides are more effective than any other dopants in improving the ionic conductivity of Li3 PS4 . Graphical abstract: Image 1 Highlights: First principles are used to study the effect of dopants on ionic conductivity of Li3 PS4 . The dopants' effect in stabilizing its moisture instability is also investigated. Cation and metal halide dopants improve the ionic conductivity of Li3 PS4 significantly. Metal oxide is the most effective in improving moisture instability of Li3 PS4 . Soft cations improve of its ionic conductivity and moisture instability simultaneously.